Over a million students use our free study notes to help them with their homework
Start on the easiest equation and solve to find yy-3x+2=0 <=> y=3x-2Then susbtitute in equation the expression of y in the second equation and simplify(3x-2)2-x-6x2=0 <=>...
The question has a number of important points which should be highlighted before beginning. Firstly the fact that the picks are at random. Secondly that the value of the coins must be at least 40p, so a t...
In order to find the coordinates of the minimum point of any curve y = f(x), you must differentiate the equation of the curve with respect to x and then equate it to zero.In this case, the differential of...
Expand the (2x + 3y)^2 term to give 4x2 + 9y2 +12xy Expand (x - 4)(4x2+ 9y2+12xy) to give (4x3+9xy2 + 12x2y - 16x2 Answered by Mohammed R. • Maths tutor4288 Views
There are two ways of solving this problem: Method 1: substitution. Make X (or Y) the subject of one equation: X= (4-6Y)/4Substitute this into the other equation:...
←
504
505
506
507
508
→
Internet Safety
Payment Security
Cyber
Essentials